PROFIL DISTRIBUSI LEMAK TUBUH DAN LEMAK DARAH DEWASA GEMUK DI PERDESAAN DAN PERKOTAAN - Fitrah Emawati; Muherdiyantiningsih Muherdiyantiningsih; Rustan Effendi; Susilowati Herman (Persagi, 2004)
THE PROFILE OF BODY FAT DISTRIBUTION AND SERUM LIPID OF THE OBESE ADULT IN RURAL AND URBAN AREA.Background: Coronary heart disease is becoming prevalent in productive age in Java and Bali, while one of the risk of coronary heart disease is dislipidemia which have correlation to obesity and overweight. Objectives: To know the profile of body fat distribution and serum lipid of the obese adult living in rural and urban area. Methods: The design of the study is correlational. The study was done in 2 sub-districts, Ranca Bungur and Tanah Sareal, Bogor. Samples of the study were adult men and women who had BMI > 25 kg/m2 and aged 30-55 years old. Results: Samples who live in urban area had higher BMI than those live in rural area (31 ± 3.8 kg/m2 vs 29 ± 2.9 kg/m2), while women live in rural area had subscapula and suprailiaca with bicep and tricep rasio (SSi-BT) slightly higher than those in urban area (1,44 ± 0.29 vs 1,32 ± 0.27). Men live in urban area had HDL and LDL cholesterol level higher than those in rural area. The concentration of cholesterol and blood pressure of samples who live in rural higher than those in urban. The activity level of women and men in urban area were lighter than those in rural area. Abdominal to hip ratio of women in rural had correlation to blood glucose and LDL level while fat distribution of women living in urban had no correlation to serum lipid. SSi-BT and abdominal to hip ratio (RLPP) of men in rural had correlation to trigliceride, on the other hand the abdominal to hlp ratio of men who lived in urban had correlation to cholesterol level. Conclusions: Fat distribution of men and women in rural area distributed to central of the body (abdominal), while women in urban area distributed to general of the body and men was mainly located in central of the body (abdominal). Abdominal to hip ratio and SSi-BT had correlation to serum lipid, but not BMI. The activity level of women and men in rural or urban had no correlation to serum lipid.Keywords: body fat distribution, serum lipid, obese adult, rural, urban